Penerapan dan Urgensi Model Model Cash Waqaf (Studi pada Hasil Jurnal Penelitian di Indonesia) - Al Amin; Refiter Putra; Hadi Subeno; Husnul Bashir; Wira Andespa; Ahmad Ridwan (Journal on Education, 2023)
Cash Waqf is an act of a Waqif who plans to donate and/or donate part of the money to a productive trust. The aim of the research is to find out the cash waqf models and their important role in Indonesia, seen from the results of the journal research. This research method is literature. The form of this research is descriptive with qualitative analysis using data sources (primary) and secondary data sources. The results of this study are the cash waqf model as a means of empowering people. This study found that cash funds were managed using a very productive waqf management model. This effort was continued with the assistance of four procurement transfer programs to the center through a virtual account. Cash Waqf Model Online Using a Modified Technology Acceptance Model. Based on the calculation results obtained, the image has a significant effect on the TAM variables, namely PEOU and PU. Cash Waqf Management Model for Housing Investment, Cash Waqf Model Using Secondary Project Pattern For side projects, funding supports the main project. Productive Cash Waqf Empowerment Model in Alleviating Poverty, The multiplier effect mechanism of cash waqf can be explained as follows, namely cash waqf funds managed by nazir to be invested generate returns with 10% paid to nazir as a management fee and 90% of the proceeds of the mauquf.